Confirmation of sex pheromone biosynthesis from (16-D3)palmitic acid in the turnip moth using capillary gas chromatography - Lofstedt, Christer; Elmfors, Anders; Sjögren, Maria; Wijk, Elisabeth (Experientia, 1986)
(16-D3)palmitic acid was applied topically to pheromone glands of the turnip moth. After incubation omega labeled analogues of fatty acid methyl esters and acetates were identified by gas chromatography with flame ionization detection and selected ion monitoring. The pheromone components (Z)-5-decenyl, (Z)-7-dodecenyl- and (Z)-9-tetradecenyl acetate were all biosynthesized from palmitic acid along a common pathway.
Keywords: Agrotis segetum; biosynthesis; capillary gas chromatography; deuterium; Lepidoptera; palmitic acid; Pheromone; polyethylene glycol